ANALISIS YURIDIS TERHADAP PELAKU PENJATUHAN TINDAK PIDANA PENCEMARAN NAMA BAIK CALON ANGGOTAN DPRD (PUTUSAN NOMOR 81/PID.SUS/2021/PN SGT): Juridical Analysis of Perpetrators of Criminal Defamation DPRD Member Candidates (Decision Number 81/Pid.Sus/2021/PN Sgt) - Gadys Thalia Noor; Azmi Syahputra (Reformasi Hukum Trisakti, 2024)
The rapid advancement of technology facilitates social interactions from the physical world to the digital realm, making it accessible to everyone, including criminal offenses like defamation on social media. The research questions are: 1) Do the elements of defamation against a prospective council member in Verdict No. 81/Pid.Sus/2021/PN Sgt comply with Article 45 in conjunction with Article 27 Paragraph 3 of the ITE Law and Article 315 of the Penal Code for minor offenses? 2) Is the two-month sentence imposed by the judge in line with the sentencing objectives under the Penal Code in Verdict No. 81/Pid.Sus/2021/PN Sgt? This research employs a normative method with secondary data, using descriptive-analytical techniques analyzed qualitatively with deductive reasoning. The findings indicate that the crime's elements do not align with the minor offense provisions of Article 315 of the Penal Code. The two-month probationary sentence does not meet the sentencing guidelines' objectives. The conclusion is that the verdict does not adequately apply Article 45 in conjunction with Article 27 Paragraph 3 of the ITE Law and Article 315 of the Penal Code, nor does it align with sentencing objectives. Judges should consider legal certainty, justice, utility, and societal values.